Central Corneal Thickness in Nepalese Glaucoma Patients and Glaucoma Suspects - Prakash Adhikari; Pratik Chettry; Madhu Thapa (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2014)
Purpose: To compare central corneal thickness (CCT) among glaucoma patients, glaucoma suspects, and normal subjects and to determine its association with glaucoma severity in Nepalese population. Methods: This study included 400 eyes (149 glaucoma, 157 glaucoma suspects, 94 controls) of 400 participants examined in a glaucoma clinic and eye OPD in Nepal. CCT was measured by ultrasonic pachymetry. Results: CCT was significantly different among the study groups (P = 0.05), with the thinnest CCT in normal tension glaucoma (NTG) and thickest in ocular hypertension (OHT). CCT (in μm) was thinner in NTG (519.6 ± 31.6; P = 0.06) and primary open angle glaucoma (POAG) (524.5 ± 35.8; P = 0.026) than controls (536.6 ± 28.9); and it was thinner in POAG compared to primary angle closure glaucoma (PACG) (541.3 ± 50.5; P = 0.028) and OHT (559.8 ± 28.1; P = 0.017). In NTG, CCT was thinner compared to Glaucoma suspects (GS) (531.6 ± 35.0; P = 0.038), PACG (P = 0.008), and OHT (P = 0.008).There was no correlation between CCT and visual field defect and CCT was not statistically different between early, moderate and severe POAG groups. Conclusions: We report that CCT in glaucoma suspects is similar to normal subjects and POAG, but thicker than NTG. These data will be important in clinically monitoring glaucoma suspects that are at increased risk of glaucoma. Our results may be population specific and further longitudinal studies are warranted to determine influence of CCT on glaucoma progression in this population.